Is reversion to PPP in euro exchange rates non-linear? - Bernd Schnatz (European Central Bank (ECB), 2006)
The paper tests for nonlinearities in the adjustment of the euro exchange rate towards purchasing power parity (PPP). It presents new survey based evidence consistent with non-linear patterns in euro exchange rate dynamics. Moreover, based on an exponential smooth transition autoregressive (ESTAR-) model, it finds strong evidence that the speed of mean reversion in euro exchange rates increases non-linearly with the magnitude of the PPP deviation. Accordingly, while the euro real exchange rate can be well approximated by a random walk if PPP deviations are small, in periods of significant deviations, gravitational forces are set to take root and bring the exchange rate back towards its long-term trend. Consistent with higher euro-dollar volatility, deviations from the PPP equilibrium for this pair need to be stronger in order to reach the same adjustment intensity as for other currencies.
Keywords: F31; 330; non-linearities; purchasing power parity; real exchange rate; STAR models; Kaufkraftparität; Euro; Wechselkurs; EU-Staaten